AMERICAN JORDAN AIDS 1977-1998 - Sukkar Khayoon, Bushra; Abdlkhdher Maarch, Haithem (International Journal of Psychosocial Rehabilitation, 2020)
The review is a survey of American and Jordanian aid. The review required an examination of Jordan and US two-sided exchange streams and monetary streams. The review is a quantitative analysis. Administrations were not in the area analysis in light of the fact that the volume of U.S.-Jordan exchange administrations is too little to be in any way reflected. The review analyzes the U.S. and Jordan imports and exports and the connection between the nations. The analysis focuses on the effect of levy evacuation and does not unequivocally represent the end or diminishment of nontariff hindrances, changes in different arrangements, or changes in help strategies between the U.S. and Jordan.